2020
DOI: 10.1039/d0ta04612d
|View full text |Cite
|
Sign up to set email alerts
|

Flexible hybrid piezo/triboelectric energy harvester with high power density workable at elevated temperatures

Abstract: Eco-friendly energy harvesters with high output for effectively harvesting mechanical energy over a broad temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The improved output performance is presented in Figure 4 D(iii), in which a significant enhancement can be noticed through this hybridization structure compared with a single mechanism. Figure 4 E shows another flexible hybrid EH with PENG and TENG ( Sun et al., 2020b ). A polyimide (PI) layer was first spin-cast onto a glass substrate and then coated with interdigital (ID) electrodes.…”
Section: Hybridized Ehs For a Single Energy Sourcementioning
confidence: 99%
“…The improved output performance is presented in Figure 4 D(iii), in which a significant enhancement can be noticed through this hybridization structure compared with a single mechanism. Figure 4 E shows another flexible hybrid EH with PENG and TENG ( Sun et al., 2020b ). A polyimide (PI) layer was first spin-cast onto a glass substrate and then coated with interdigital (ID) electrodes.…”
Section: Hybridized Ehs For a Single Energy Sourcementioning
confidence: 99%
“…To achieve a good performance at high temperature, Sun et al reported a soft hybridized PENG-TENG (Figure 3D) on the basis of piezoelectric ceramic particles. This device exhibited good temperature stability at a temperature of 200 C and can generate an output power of 560 nA and 150 V (Sun et al, 2020). Chen et al analyzed the basic principle of contactmode hybridized generator (Figure 3E) from the transfer of charge, current, voltage, and average output power from hybridized nanogenerator's material properties, structural parameters, and operational conditions.…”
Section: Hybridized Piezoelectric-triboelectric Nanogeneratormentioning
confidence: 99%
“…[70][71][72] Hybridized devices combining the characteristics and advantages of the two prominent mechanisms have also been thoroughly investigated to further extend the systematic performance and capability in divergent applications. [73][74][75][76] Typically, lower-limb rehabilitation is desperately in need of a wearable mobile machine, i.e., exoskeleton, to support and assist the lower-limb motion of the patients suffering from impaired ambulation. [77,78] Due to the high requirement on structural strength and endurance, the exoskeletons are mostly constructed with rigid mechanical components that wrap around the lower limb and designed with movable joints to allow for the free movement of the lower limb.…”
Section: Introductionmentioning
confidence: 99%
“…[ 70 , 71 , 72 ] Hybridized devices combining the characteristics and advantages of the two prominent mechanisms have also been thoroughly investigated to further extend the systematic performance and capability in divergent applications. [ 73 , 74 , 75 , 76 ]…”
Section: Introductionmentioning
confidence: 99%